KECEMASAN DALAM PENGAMBILAN KEPUTUSAN KARIER PADA REMAJA - Ezra Addo Setiawan; Anniez Rachmawati Musslifah (Sekolah Tinggi Agama Buddha Nalanda, 2023)
The purpose of this study is to determine how insecure young people feel when making career decisions. Adolescents experience confusion, or anxiety, when making career development decisions. Fear of what hasn't happened yet, fear of failure, and lack of support from the environment. The method used in this study is a qualitative method. The subjects of this study were late adolescents, with a total of 3 respondents aged 17 to 19. Direct observation and interview techniques were used as data collection techniques in this study. The study found that young people surveyed reported feeling anxious when contemplating career decisions. This was due to worrying about things that hadn't happened yet, fear of failure before trying, lack of self-confidence, and lack of parental and community support. Research results on adolescents' anxiety during career decision-making have shown that adolescents' anxiety has a significant impact on their ability to make decisions. Therefore, the lower an adolescent's anxiety, the better he/she will be in decision making.